The Influence of Technology, Financial Literacy, and Ease of Using E-Wallets on Consumers of Mall Boemi Kedaton Supermarket - Candrakanta, Cheryl; Pujiati, Pujiati; Rufaidah, Erlina (FKIP Universitas Lampung, 2023)
The development of the times has influenced changes in various areas of life, one of which is finance. The financial field that has undergone changes is transaction activities. In the past, transaction payment activities were carried out by exchanging goods or barter, but at this time it is developing using digital-based transaction payments. These changes occur due to technological advances, financial understanding, and the development of the digital economy. This study aims to determine the influence of technological advances, financial literacy, and perceptions of ease of use of e-wallets on consumers of Chandra supermarket Mall Boemi Kedaton Bandar Lampung. This research is quantitative using descriptive verifiative methods with ex post facto approach and surveys. Sampling in this study used a non-probability sampling method with purposive sampling techniques. The population in this study was consumers of Chandra supermarket Mall Boemi Bandar Lampung with 75 consumers as a sample. The data analysis method uses SPSS version 25 by testing the hypothesis through a simple linear regression test and multiple regression test. This research reveals that technological advancements, financial literacy, and perceived convenience have a positive effect on the use of e-wallets. These three factors play an important role in increasing the tendency of consumers to choose and utilize e-wallets in their digital transactions.Keywords: E-Wallet, Convenience, Financial Literacy, TechnologyDOI: http://dx.doi.org/10.23960/E3J/v6i2.176-181